INTEGRATING STATE EDUCATION STANDARDS IN TRAINING PERSONNEL IN THE FIELD OF CONSTRUCTION - Tashkoziyeva, Zulfiya Eraliyevna (Educational Research in Universal Sciences, 2023)
For students of fine arts and engineering graphics in the future, to show their technical ideas through a drawing, illustrated the principle of operation on the drawing of any item or objects and to understand and imagine the structural structure, modern design requirements is to give knowledge, skills and qualifications to receive.